Konsep Pendidikan Komunikasi dan Kebudayaan - Sri Tuti Rahmawati (Journal on Education, 2023)
This study examines the concept of Communication and Culture Education. The study of cross-cultural communication cannot be separated from culture because in cross-cultural communication the communication participants are faced with the problem of cultural differences. This type of research uses a descriptive type which aims to make a systematic, factual and accurate description or picture of facts, characteristics and the relationship between phenomena in the object of research according to the problems studied. The results of this study are; a. Communication Relations with Culture, b. The Cruciality of Cultural Differences, c. Prejudice. The situation in cross-cultural communication is so dynamic and evolving and sometimes not free from stereotypes. In cross-cultural communication there is an exchange between one culture and another. The cultural pressure point in the context of cross-cultural communication has more to do with immaterial cultural aspects, such as language, traditions, habits, customs, moral norms and values, ethics, ideas, religion, arts, beliefs, and so on.